Dragon Day - Stan!, 1964-; Rams, Vinod (Renton, WA : Mirror Stone/Wizards of the Coast ; [New York] : Distributed in the U.S. by Holtzbrinck, 2005)
Two of the campanions end up taking opposing sides in the feud between the wizards and clerics of Solamnia.
010-up.
Accelerated Reader AR
Keywords: Friendship -- Juvenile fiction; Wizards -- Juvenile fiction; Imaginary wars and battles -- Juvenile fiction; Krynn (Imaginary place) -- Juvenile fiction; Magic -- Juvenile fiction